Union of the Comoros : Third Review Under the Three-Year Arrangement Under the Extended Credit Facility, Requests for Waiver of Nonobservance of a Performance Criterion, Modification of a Performance Criterion, Extension of the Arrangement, Rephasing of Disbursements, and Financing Assurances Review. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2013)
Comoros remains in debt distress, pending the achievement of the completion point under the Highly Indebted Poor Country (HIPC) Initiative. The outlook for 2012 is broadly consistent with expectations under the Extended Credit Facility (ECF) arrangement. The IMF Executive Board has approved a three-year ECF arrangement to support Comoros' medium-term economic recovery efforts. The government has continued pursuing a prudent external debt management policy. Achievement of the government's fiscal objectives requires close adherence to the fiscal program to enhance the efficiency of tax and customs administration and to expand the tax base.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet